Construction and electronic properties of carbon nanotube hybrids with conjugated cubic silsesquioxane. (27th August 2015) - Xu, Kai; Lin, Weihong; Wu, Jiancheng; Peng, Jun; Xing, Yuxiu; Gao, Shuxi; Ren, Yuanyuan; Chen, Mingcai
Abstract : Hierarchical zero-dimensional cubic silsesquioxane/one-dimensional SWNT hybrids provided excellent charge transfer and synergistic effects compared to both SWNTs and OASQ. Abstract : We herein report a hierarchical hybrid prepared from zero-dimensional cubic silsesquioxane, octa-aminophenylsilsesquioxane, and one-dimensional single-walled carbon nanotubes (SWNTs) through Friedel–Crafts acylation and amidation chemistry. We characterized the electronic structure and morphology of the nanohybrid by FT-IR spectroscopy, Raman spectroscopy, electrochemical analysis and field-emission scanning electron microscopy. In addition, high resolution TEM results indicated that their average diameter and diameter distribution remained nearly unchanged with respect to that of the pristine, in accordance with the Raman spectroscopic results. The specific capacitance of the obtained hybrid was larger than that of the pristine SWNTs due to its hierarchical structure and the charge transfer from both SWNTs and octa-aminophenylsilsesquioxane. To further study the electronic properties of conjugated functionalized silsesquioxane, the model compounds with a structure similar to that of the nanohybrid were designed and characterized by photoluminescence UV-vis analysis and density functional theoretical calculations. The analysis indicated the presence of an electron delocalization effect between the octa-aminophenylsilsesquioxane cores and the conjugated group. Such important electronic properties also assisted in the improvement of the performance of the hierarchical hybrid.